New perspectives in philosophy of education : ethics, politics and religion - Lewin, David; Guilherme, Alexandre; White, Morgan (Bloomsbury Academic, 2014)
"New Perspectives in Philosophy of Education seeks to build a bridge between philosophical reflection and socio-political action by developing a range of critical discussions in the areas of ethics, politics and religion. This volume brings together established authorities and a new generation of scholars to ask whether philosophy of education can contribute to political and social discourse, or whether it is destined to remain the marginal gadfly of mainstream ideology. The philosophy of education stands in danger of becoming a neglected field at precisely the moment we need to be able to reflect upon the increasingly apparent costs of the technocratic attitude to education. While many of the educational policy discussions of recent years seem far-reaching and radical, critical debate surrounding these initiatives remain largely at a populist level. New Perspectives in Philosophy of Education provides contemporary responses to philosophical issues that bear upon educational studies, policies and practices, contributing to the debate on the role of philosophy of education in an increasingly fractured intellectual milieu"--Resumé vydavatele
Keywords: filozofie výchovy; sociologie výchovy; philosophy of education; educational sociology; eseje; essays